Analisis Drag dan Lift pada Variasi Bentuk After Body Kapal Selam Mini dengan Metode Computational Fluid Dynamics - Putri Virliani; I Ketut Suastika; Wasis Dwi Aryawan (Universitas Muhammadiyah Sidoarjo, 2017)
One aspect that needs to be studied in submarine design is the hydrodynamic aspect relating to submarine maneuverability. This research begins by calculating the value of drag and lift on the three variations of the after body’s mini submarine. The first variation as the initial design is rudder and stern plane arranged perpendicularly or named the+ Stern. Then for the second variation made changes to the arrangement of rudder and stern plane in the after body of the mini submarine with + Stern arrangement, the rudder arranged each other crossed so that it resembles the letter X and called the X-Stern arrangement. Further, for the third variation, the upper rudder of the X-Stern arrangement is replaced by the upper rudder of the + Sternarrangement so that it resembles the inverted Y letter and is called the Y-Stern arrangement. Drag and lift are calculated numerically by using ANSYS-CFX software. From the calculation of CFD found that the submarine with after-body Y-Stern arrangement has the smallest drag and lift value.